Stellar alchemy : the celestial origin of atoms - Cassé, Michel, 1943- (Cambridge University Press, 2003)
When Cortez asked the Aztecs where they obtained the iron in their daggers, they pointed to the sky. Stars manufacture iron, and every other element making up familiar objects around us. In this fascinating book Michel Cassé explains how even humanity itself is connected to the debris of exploded stars.